2013
DOI: 10.1109/tpel.2013.2251358
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Diagnostics and Prognostics of Wire Bonding Faults in IGBT Modules for Electric Vehicle Drives

Abstract: Abstract-ThisHowever, IGBTs are known to be prone to failure [12]-[19], and the situation would only get worse when operating in the harsh environment beneath the bonnet of an electric vehicle. ) have received much attention by the industry. Nonetheless, when the bonding using these new technologies fails, the entire device will be damaged with catastrophic consequences.Without a doubt, the detection of an IGBT fault prior to (prognosis) or even after (diagnosis) its occurrence is of critical importance to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(134 citation statements)
references
References 55 publications
(12 reference statements)
0
122
0
Order By: Relevance
“…This is perhaps why there are a variety of aging trends reported in the literature when examining the forward voltage of a device. For example, increases in the forward voltage in IGBTs of 5%, 7%, and 20% have been reported before module failure occurs [7,9,11,15]. At the same time, decreases of up to 25% were present in other studies [7,16,18].…”
Section: Background: Reliability and Condition Monitoring Of Power Sementioning
confidence: 89%
See 1 more Smart Citation
“…This is perhaps why there are a variety of aging trends reported in the literature when examining the forward voltage of a device. For example, increases in the forward voltage in IGBTs of 5%, 7%, and 20% have been reported before module failure occurs [7,9,11,15]. At the same time, decreases of up to 25% were present in other studies [7,16,18].…”
Section: Background: Reliability and Condition Monitoring Of Power Sementioning
confidence: 89%
“…The majority of research has focused on monitoring an electrical parameter that indicates degradation. Examples of the most commonly monitored parameters are: the forward voltage in IGBTs (or the on-state resistance in MOSFETs) [9][10][11] and the evolution of a module's thermal resistance (Rth) [12][13][14][15][16]. These parameters have been studied since the 1990s.…”
Section: Background: Reliability and Condition Monitoring Of Power Sementioning
confidence: 99%
“…Although, prognostic approaches can also be employed in system diagnostics, but the main challenge occurs in situations where the fault was sudden, which means prognostics will fail to make a viable prediction. Due to IVHM needs, requirements to automotive diagnostic protocols is increased during last few years because future vehicles are highly equipped with low power electronics in almost any equipment (even components) such as electronic fuel injection, automatic gear box, etc [13]. Having more electronic featured components and systems will require additional care toward resilient trustworthy cyber-physical systems as safety, security and privacy issues may affected by, for instance, by hackers, hardware and software Trojans [4] [14].…”
Section: Reliability Information From Ivhm Perspectivementioning
confidence: 99%
“…Nowadays, it is well understood that one of the most vulnerable component that current EVs' are suffering from their failures is IGBT that brings limitation on safety and economic issues of EVs [13]. Alghassi et al has discussed different failures mechanisms related to IGBT and they have also presented prognosis model for the dominant failure at a component level in [21] [22].…”
Section: A Dc-dc Convertermentioning
confidence: 99%
“…IGBT is one of the most widely used power modules in power electronic converters, and its reliability has drawn much attention since it is one of the most fragile components in power converters [1][2][3]. Researches have shown that the thermal behavior of IGBT has a significant effect on the reliability of the power conversion system.…”
Section: Introductionmentioning
confidence: 99%